Cybersecurity: a critical priority for digital mental health - Inkster, Becky; Knibbs, Catherine; Bada, Maria (Frontiers in Digital Health, 2023)
There has been a surge in the supply and demand of digital mental health support services in recent times. There have also been high profile cyberattacks specifically targeting mental health and behavioral services, along with a shift toward targeting vulnerable people directly. Cyberattacks involving personal health data, especially sensitive mental health data, could have devastating consequences to vulnerable people, those close to them, and many other stakeholders. This article calls for the immediate examination of the current state of cybersecurity in the digital mental healthcare industry to collectively identify risks and to protect user and provider vulnerabilities. This article points to the need to build a global cybersecurity culture within digital mental health while also working closely with other industries. The article concludes by making some preliminary recommendations to help support the creation of standards that will enhance the collective preparedness for future responses to cybersecurity threats and attacks.